Clinical characteristics and outcomes in Asian patients with heart failure with mildly reduced ejection fraction - Julian Cheong Kiat Tay; Shaw Yang Chia; Siew Hui Michelle Koh; David Kheng Leng Sim; Ping Chai; Seet Yoong Loh; Fazlur Rehman Jaufeerally; Sheldon Shao Guang Lee; Patrick Zhan Yun Lim; Jonathan Yap (Singapore Medical Journal)
Introduction: Data on heart failure (HF) with mildly reduced ejection fraction (HFmrEF) is still emerging, especially in Asian populations. This study aims to compare the clinical characteristics and outcomes of Asian HFmrEF patients with those of HF patients with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). Methods: Patients admitted nationally for HF between 2008 and 2014 were included in the study. They were categorised according to ejection fraction (EF). Patients with EF <40%, EF 40%–49% and EF ≥50% were categorised into the following groups: HFrEF, HFmrEF and HFpEF, respectively. All patients were followed up till December 2016. Primary outcome was all-cause mortality. Secondary outcomes included cardiovascular death and/or HF rehospitalisations. Results: A total of 16,493 patients were included in the study — HFrEF, n = 7,341 (44.5%); HFmrEF, n = 2,272 (13.8%); and HFpEF n = 6,880 (41.7%). HFmrEF patients were more likely to be gender neutral, of mid-range age and have concomitant diabetes mellitus, hyperlipidaemia, peripheral vascular disease and coronary artery disease (P < 0.001). The two-year overall mortality rates for HFrEF, HFmrEF and HFpEF were 32.9%, 31.8% and 29.1%, respectively. HFmrEF patients had a significantly lower overall mortality rate compared to HFrEF patients (adjusted hazard ratio [HR] 0.89, 95% confidence interval [CI] 0.83–0.95; P < 0.001) and a significantly higher overall mortality rate (adjusted HR 1.25, 95% CI 1.17–1.33; P < 0.001) compared to HFpEF patients. This was similarly seen with cardiovascular mortality and HF hospitalisations, with the exception of similar HF hospitalisations between HFmrEF and HFpEF patients. Conclusion: HFmrEF patients account for a significant burden of patients with HF. HFmrEF represents a distinct HF phenotype with high atherosclerotic burden and clinical outcomes saddled in between those of HFrEF and HFpEF. Further therapeutic studies to guide management of this challenging group of patients are warranted.